Devilish fun

Algebra Level 4

The product of the real roots of the polynomial

f ( x ) = x 4 4 x 3 + 6 x 2 4 x 666 f(x) = x^4 - 4x^3 + 6x^2 -4x-666

can be written as a b a - \sqrt{b} , where a a and b b are positive integers. What is the value of a + b a+b ?


The answer is 668.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Aaron Doman
Sep 22, 2013

We have f ( x ) = ( x 1 ) 4 667 f(x)=(x-1)^4-667 , so the real roots must satisfy ( x 1 ) 2 = 667 (x-1)^2=\sqrt{667} x 2 2 x + 1 667 = 0. x^2-2x+1-\sqrt{667}=0. By Vieta's, the product of the roots is 1 667 1-\sqrt{667} , so a + b = 668 a+b=\boxed{668} .

Moderator note:

Good explanation. Blind application of Vieta led many to claim that the product must be 666 -666 .

x 4 4 x 3 + 4 x 2 + 2 x 2 4 x 666 x^{4} - 4x^{3} + 4x^{2} + 2x^{2} - 4x - 666

x 2 ( x 2 + 4 4 x ) + 2 x ( x 2 ) 666 x^{2}(x^{2} + 4 - 4x) + 2x(x - 2) - 666

( x ( x 2 ) ) 2 + 2 x ( x 2 ) 666 = 0 (x(x-2))^{2} + 2x(x-2) - 666 = 0

( x 2 2 x + 1 ) 2 = 667 (x^{2} - 2x + 1)^{2} = 667

( x 1 ) 4 = 667 (x - 1)^{4} = 667

x = 1 ± 667 4 x = 1 \pm \sqrt[4]{667}

U Z - 6 years, 6 months ago

Nicely Done !!

Henrique Mf - 7 years, 8 months ago

Challenge Master, why does Vieta's Formula not apply to the original fourth degree polynomial?

Alex Porush - 7 years, 8 months ago

Log in to reply

The question is asking for the product of the real roots, but two of the roots of the original polynomial are nonreal.

Aaron Doman - 7 years, 8 months ago

Log in to reply

Aha! Thanks :)

Alex Porush - 7 years, 8 months ago

A nice tricky problem. Observe that f ( x ) = 4 ( x 3 3 x 2 + 3 x 1 ) = 4 ( x 1 ) 3 f'(x) = 4(x^3 - 3x^2 + 3x - 1) = 4(x-1)^3

Integrating both sides & using f ( 0 ) = 666 f(0)=-666 , we get: f ( x ) = ( x 1 ) 4 667 f(x) = (x-1)^4 - 667

At f ( x ) = 0 f(x)=0 , ( x 1 ) 4 = 667 ( x 1 ) 2 = ± 667 (x-1)^4 = 667 \Rightarrow (x-1)^2 = \pm \sqrt{667}

We neglect ( x 1 ) 2 = 667 (x-1)^2 = - \sqrt{667} ,as it contributes to complex roots & take ( x 1 ) 2 = 667 (x-1)^2 = \sqrt{667} , whose roots are the desired reals. Expanding, x 2 2 x + ( 1 667 ) = 0 x^2 - 2x +(1-\sqrt{667}) = 0 . So product of the required roots is 1 667 1-\sqrt{667} .

Nice way to break the problem! Although I could figure out the ( x 1 ) 4 (x-1)^4 hidden in the expression, this method would be useful at times :D

Parth Thakkar - 7 years, 3 months ago
Harrison Lian
Sep 23, 2013

When we examine the equation, we see that it looks very similar to ( x 1 ) 4 = x 4 4 x 3 + 6 x 2 4 x + 1 (x-1)^4=x^4-4x^3+6x^2-4x+1 .

Therefore, we add 667 to both sides to get x 4 4 x 3 + 6 x 2 4 x + 1 = 667 ( x 1 ) 4 = 667 x 1 = 667 4 x = 1 ± 667 4 x^4-4x^3+6x^2-4x+1=667 \implies (x-1)^4=667 \implies x-1= \sqrt[4]{667} \implies x=1 \pm \sqrt[4]{667}

Therefore, when we multiply ( 1 + 667 4 ) ( 1 667 4 ) (1+\sqrt[4]{667}) (1-\sqrt[4]{667}) , we get 1 667 Which implies that our final answer is 668 1-\sqrt{667} \text{ Which implies that our final answer is } \boxed{668}

First notice that the first 4 terms are the expansion of the first 4 terms in (x + 1)^4. We can rewrite the function as (x + 1)^4 - 667 = 0. Then (x + 1)^4 = 667. Take the square root of both sides which gives (x + 1)^2 = sqrt(667). The two non real solutions are found when (x + 1)^2 = -sqrt(667). Since the question asks for the product of the real roots we only need to look at the first equation, (x + 1)^2 = sqrt(667). This tells you that the two values of x are 1 - 4th root(667) and 1 + 4th root(667). The product of the two solutions is 1 - sqrt(667). Hence, the sum of a and b is 668.

It should have been ( x 1 ) 2 (x - 1)^2 .

Akshat Jain - 7 years, 8 months ago
Jan J.
Sep 23, 2013

Looking at the coefficients of f ( x ) f(x) one can feel that the polynomial is symmetric, indeed the polynomial is symmetric about the x = 1 x = 1 axis. Hence f ( 1 x ) = f ( 1 + x ) f(1 - x) = f(1 + x) How we found the axis of symmetry? Well, note that f ( x ) = 4 ( x 1 ) 3 f'(x) = 4(x - 1)^3 Hence f ( x ) f(x) attains minimum if and only if x = 1 x = 1 , checking that it is also axis of symmetry is trivial. And now we just proceed easily noting that f ( 1 x ) = x 4 667 = ( x 667 4 ) ( x + 667 4 ) ( x 2 + 667 ) \begin{aligned} f(1 - x) &= x^4 - 667 \\ &= \left(x - \sqrt[4]{667}\right) \cdot \left(x + \sqrt[4]{667}\right) \cdot \left(x^2 + \sqrt{667}\right) \end{aligned} This has roots ± 667 4 \pm \sqrt[4]{667} and ± i 667 4 \pm i\sqrt[4]{667} . Hence f ( x ) f(x) has roots 1 ± 667 4 1 \pm \sqrt[4]{667} , 1 ± i 667 4 1 \pm i\sqrt[4]{667} , so the product of the real roots is ( 1 667 4 ) ( 1 + 667 4 ) = 1 667 \left(1 - \sqrt[4]{667}\right) \cdot \left(1 + \sqrt[4]{667}\right) = 1 - \sqrt{667} Hence a + b = 1 + 667 = 668 a + b = 1 + 667 = \boxed{668}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...